Development Of a Sustainability Accounting Model Based on a Pentuple Bottom Line for UB Forest Wooden Crafts Production - Sukoharsono, Eko Ganis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to develop young farmers at UB Forest as souvenir wood craftsmen using a sustainable accounting model based on the triple bottom line. This study was conducted using a participatory method involving the community and youth around UB Forest. Community participation in the community service that has been implemented is quite high, indicated by the community's enthusiasm in carrying out a series of programmed activities. The results of this study are that the people (social) aspect focuses on improving the skills and insights of the community and youth around UB Forest regarding wood crafts and their potential for development. The planet (environmental) aspect focuses on utilizing UB Forest's natural resources without damaging the environment and biodiversity in UB Forest and practicing environmental sustainability. The profit (economic) aspect focuses on increasing income and creating alternative incomes for the community and youth in the UB Forest area. Increased income is obtained from the sale of wood crafts in the form of souvenirs and other products. The phenol technology aspect focuses on the introduction of new and modern technologies that can be used in the production process. Currently, modern technology cannot be used because the wood craft business is still in the development stage, so a technological needs analysis is needed first. Furthermore, the prophetic (spiritual) aspect focuses on enhancing the spirituality of the community and youth in the UB Forest area. This spiritual enhancement is implemented through religious education in the form of spiritual studies involving religious leaders.